THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER LOYALTY AT CAFE NGOPI SANTAI IN MAKASSAR CITY - Yohanis Resa Surentu; Agus Syam; Asmayanti; Muhammad Jufri; Sumiati Tahir (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The increasing lifestyle of society that is continuously evolving in this era, along with the advancement of increasingly sophisticated technology and the ever-developing lifestyle of the community, certainly impacts the business world. The current business development is so rapid that companies are required to be more focused and always innovate so that they can survive in the tight competition, especially in the café business. 1) To prove whether there is a significant influence of product quality on customer loyalty at the Ngopi Santai café. 2) To prove whether there is a significant influence of service quality on customer loyalty at the café ngopi santai. 3) To prove whether there is a significant influence of product quality and service quality on customer loyalty at the café ngopi santai. This research uses a quantitative method with multiple regression analysis techniques to analyze the collected data, and the instrument used is a questionnaire. The population in this study consists of all customers of Café Ngopi Santai who have visited and purchased products from Café Ngopi Santai. The sample for this research was determined using accidental sampling, which means respondents who were coincidentally encountered by the researcher during the research period and have the potential to be data sources and are willing to participate in this study, totaling 100 respondents. The results of this study indicate that: 1) There is a significant influence of product quality on customer loyalty at the Ngopi Santai café in Makassar. 2) There is a significant influence of service quality on customer loyalty at the Ngopi Santai café in Makassar. 3) There is a significant influence of product quality and service quality on customer loyalty at the Ngopi Santai café in Makassar city.